Factors influencing the change in the sense of place of markets in urban regeneration - Abd Ghapar, Muhammad Hazrin; Zakariya, Khalilah; Harun, Nor Zalina; Zen, Ismawi (IDOSI Publications, 2016)
The development of markets is essential to the growth of the urban economy and in strengthening the sense of place of the city. In the process of urban regeneration, some urban markets with tourism potentials have been redeveloped to upkeep with the city’s modernization. The attempts to redevelop markets can either be successful or not, which consequently influence changes in the sense of place. Based on conducting a literature review on five urban market studies, this paper examines the factors that influenced the change in the sense of place of the markets, by comparing the successfully regenerated markets with those which are not. This study found three key influencing factors. First, the interactions and relationships among the market’s community can influence the strengthening or the weakening of the sense of place. Second, the physical setting influenced on how people view the market, whether it can fulfil their needs of activity or not. Third, the image represented by the market is important in reinforcing the unique culture of the market. This study concludes that the sense of place of urban markets is vital to be identified and understood to ensure that the market’s operations continue to flourish after its regeneration.